Reimagining To Kill a Mockingbird - Austin Sarat, Martha Merrill Umphrey (University of Massachusetts Press, 2013)
The year 2012 marked the fiftieth anniversary of the release of To Kill a Mockingbird, the film remake of Harper Lee’s acclaimed novel.1 In taking note of that milestone, this volume looks at the film, a classic and canonical text in legal scholarship, with fresh eyes. The chapters that follow revisit and examine Atticus, Scout, and Jem Finch, their community, and the events that occur there through the interdisciplinary prism of law and humanities scholarship—work that brings a distinctive interpretive framework to the study of law. The film and novel are of course widely available and have taken on both a mythical and a pedagogical role in American culture (and beyond). Earnest teachers have for generations urged schoolchildren to understand Atticus Finch’s defense of Tom Robinson as a linchpin moment in the nation’s narrative of racial progress. Indeed on one standard reading, To Kill a Mockingbird is a profoundly pedagogical text, one that strives to teach us ways of overcoming prejudice and to live with one another in a better and more just world. That rendering of the film situates it in a past moment that has been overcome, and conjures Atticus Finch as a hero who, while failing in the narrative space of the film, nevertheless paves a path to a better future through his work and his children.The readings of the film offered in this volume complicate without fully rejecting that mythologizing interpretation. They peel back the film’s visual representation of Maycomb, Alabama’s many-layered social world, offering sometimes counterintuitive rereadings through the prism of number of provocative contemporary theoretical and interpretive questions.